Integrated Marketing Communication Strategy in Insurance Business Competition (Case Study of Allianz Life Indonesia Insurance in North Penajam Paser Regency) - Priyanto, Adi; Sukmarini, Andi Vita; Mujahid, Mujahid (Journal of Management and Administration Provision, 2023)
This research aims to analyze integrated marketing communication strategies in insurance business competition (Case Study of Allianz Life Indonesia Insurance in North Penajam Paser Regency) with various supporting and inhibiting factors. The research method used is descriptive qualitative with data collection through in-depth interviews and documentation. Data analysis uses participatory observation. The results of the research show that, of the 5 (five) indicators in the integrated marketing communication strategy, there are 4 (four) strategies implemented by Allianz agents in North Penajam Paser Regency, namely advertising, direct marketing, sales promotion and personal sales, although they are still less than optimal. The result of the stidy showed that Allianz agents in North Penajam Paser Regency have implemented integrated marketing communication strategies, especially personal selling and sales promotion strategies which are most dominantly used by Allianz agents in the competitive insurance business in North Penajam Paser Regency.